The time-varying impact of systematic risk factors on corporate bond spreads - Arne C. Klein; Kamil Pliszka (Deutsche Bundesbank, 2018)
During the global financial crisis, stressed market conditions led to skyrocketing corporate bond spreads that could not be explained by conventional modeling approaches. This paper builds on this observation and sheds light on time-variations in the relationship between systematic risk factors and corporate bond spreads. First, we apply Bayesian model averaging to a battery of candidate variables for determining meaningful systematic risk factors. Second, Markov switching techniques provide us with an endogenous separation of regimes accounting for times of stress, on the one hand, and for normal market conditions, on the other. Our evidence for market indices of euro-denominated bonds suggests that systematic risk factors play a much more prominent role during periods of market turmoil. Most important, expectations about default rates seem to be much more driven by systematic factors rather than idiosyncratic components during times of market stress.
Keywords: G01; G10; G11; G12; G14; G15; G32; 330; asset pricing; banking regulation; Bayesian model averaging; credit spreads; European bond market; Markov switching